Tổng hợp một số alpha,beta-không no đi từ 3-axetyl-7-metoxi-4-metylcumarin - Thảo, Nguyễn Minh; Thuấn, Nguyễn Văn; Thu Ninh, Nguyễn Thị; Thanh, Nguyễn Ngọc (Vietnam Journal of Chemistry, 2014)
Fourteen a,b-unsaturated ketones have been synthesized by reaction of 3-acetyl-7-methoxy-4-methylcoumarin with  aromatic aldehydes. Structure of these products was confirmed by IR, 1H-NMR and MS spectroscopic data. Biological activities of these compounds have been investigated